The Performance of a Bare Machine Email Server - Ford Jr., George H.; Karne, Ramesh K.; Wijesinha, Alexander L.; Appiah-Kubi, Patrick (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
Bare machine applications run directly over the hardware without using an operating system or a hard disk. This paper studies the performance of a bare machine email server whose design and implementation is based on several novel architectural features with a view towards optimizing performance. The results are compared with those for the AxiGen and ShareMailPro email servers, and a lean Java-based email server prototype running on Windows whose application-level operation closely matches that of the bare machine email server. For 80,000 emails in a LAN environment, the bare Machine server processing time is approximately 2 times faster than a Java-based server, and 2.4 times faster than the AxiGen server. For 5,500 emails in a WAN environment, the bare machine server performed at least 1.8 times faster than the Java-based and ShareMailPro servers. The results indicate that the bare machine email server outperforms the conventional email servers in LAN and WAN environments, and demonstrate the capability of using bare machines to build high-performance email servers.